2010
DOI: 10.1021/es902575d
|View full text |Cite
|
Sign up to set email alerts
|

Micropollutant and Sludge Characterization for Modeling Sorption Equilibria

Abstract: The sorption of hydrophobic micropollutants in sludge is one of the major mechanisms which drive their fate within wastewater treatment systems. The objective of this study was to investigate the influence of both sludge and micropollutant characteristics on the equilibria of sorption to particles and to dissolved and colloidal matter (DCM). For this purpose, the equilibrium constants were measured for 13 polycyclic aromatic hydrocarbons, 5 polychlorobiphenyls and the nonylphenol, and five different sludge typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 40 publications
(83 reference statements)
0
25
0
Order By: Relevance
“…In SupSS, DCM proportion was enhanced without the denaturing phenomenon reported for thermal treatment [29]. According to the bioavailability hypotheses previously mentioned in Section 3.4, micropollutant bioavailability may have been increased.…”
Section: Influence Of the Addition Of Dissolved And Colloidal Matter mentioning
confidence: 68%
See 3 more Smart Citations
“…In SupSS, DCM proportion was enhanced without the denaturing phenomenon reported for thermal treatment [29]. According to the bioavailability hypotheses previously mentioned in Section 3.4, micropollutant bioavailability may have been increased.…”
Section: Influence Of the Addition Of Dissolved And Colloidal Matter mentioning
confidence: 68%
“…Extraction from inlet and outlet sludge samples and quantification in all extracts were performed in accordance with Barret et al. [29].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In most cases, only overall removal efficiencies were determined (Simonich et al, 2002;Clara et al, 2005;Gö bel et al, 2007;Vieno et al, 2007;Smook et al, 2008;Radjenovic et al, 2009), while few studies identified and quantified the removal efficiencies related to the different mechanisms Carballa et al, 2007a;Hoori et al, 2007;Wick et al, 2009;Xue et al, 2010). Activated sludge has proved to achieve a significant removal of many micropollutants (Joss et al, 2005), mostly due to biodegradation or to sorption on solids or colloids (Barret et al, 2010), but little is known about the influence of operational parameters on both mechanisms, which might explain the disparity of removal efficiencies found for similar technologies in the literature (Onesios et al, 2009). Hydraulic retention time (HRT) together with sludge retention time (SRT) govern both reaction time and loading (McAdam et al, 2010), thus affecting biomass activity and concentration.…”
Section: Introductionmentioning
confidence: 99%